Activin A Signaling Regulates IL13Rα2 Expression to Promote Breast Cancer Metastasis - Kalli, Maria; Mpekris, Fotios; Wong, Chen K.; Panagi, Myrofora; Ozturk, Sait; Thiagalingam, Sam; Stylianopoulos, Triantafyllos; Papageorgis, Panagiotis (Frontiers in Oncology, 2019)
Metastatic dissemination of cancer cells to distal organs is the major cause of death for patients suffering from the aggressive basal-like breast cancer (BLBC) subtype. Recently, we have shown that interleukin 13 receptor alpha 2 (IL13Rα2) is a critical gene that is overexpressed in a subset of BLBC primary tumors associated with poor distant metastasis-free survival (DMFS) and can promote extravasation and metastasis of breast cancer cells to the lungs. However, the upstream signaling mechanisms that promote aberrant IL13Rα2 expression during tumor progression remain unknown. Driven by our previously published gene expression microarray data derived a well-characterized cell line model for basal-like breast cancer progression we show that both Inhibin βA (INHBA) and IL13Rα2 genes exhibit similarly higher expression levels in metastatic compared to non-metastatic cells and that overexpression of both genes predicts worse metastasis-free survival of patients with high grade tumors. Activin A, a member of the TGFβ superfamily comprising two INHBA subunits, has been shown to play context-depended roles in cancer progression. Here, we demonstrate that INHBA depletion downregulates IL13Rα2 expression in metastatic breast cancer cells, whereas treatment with Activin A in non-metastatic cells increases its expression levels. We also find that Activin A predominantly induces Smad2 phosphorylation and to a lesser extent activates Smad3 and Akt. Interestingly, we also show that Activin A-mediated upregulation of IL13Rα2 is Smad2-dependent since knocking down Smad2 or using the ALK4/ALK5 inhibitors EW-7197 and SB-505124 abolishes this effect. Most importantly, our data indicate that knocking-down INHBA levels in breast cancer delays primary tumor growth, suppresses migration in vitro and inhibits the formation of lung metastases in vivo. Conclusively, our findings presented here suggest that the development of therapeutic interventions employing small molecule inhibitors against Activin receptors or neutralizing antibodies targeting Activin A ligand, could serve as alternative approaches against breast tumors overexpressing INHBA and/or IL13Rα2.